Joint replacement risk is markedly increased in alkaptonuria (AKU) in those with prior arthroplasty - L.R. Ranganath; M. Khedr; B.P. Norman; J.H. Hughes; R. Imrich; J.B. Arnoux; B. Olsson; M. Rudebeck; J.A. Gallagher; G. Bou-Gharios (Molecular Genetics and Metabolism Reports, 2024)
Background: Increased homogentisic acid (HGA) in alkaptonuria (AKU) causes severe arthritis. Nitisinone reduces the production of HGA, but whether it also decreases arthroplasty was examined in 237 AKU patients. Patients and methods: Patients attending the United Kingdom National Alkaptonuria Centre (NAC) and the Suitability of Nitisinone in Alkaptonuria 2 (SONIA 2) study were studied. Assessments included questionnaires eliciting details of arthroplasty. Nitisinone was administered from baseline, 2 mg in the NAC and 10 mg in SONIA 2. In SONIA 2, subgroups consisted of those with baseline arthroplasty on and not on nitisinone (BR + N+, BR + N-), as well as those without baseline arthroplasty on and not on nitisinone (BR-N+, BR-N-). Results: In the SONIA2 subgroups, new joint replacement (JR) probabilities after baseline were significantly different (BR + N+, BR + N-, BR-N+, BR-N-) (χ2 = 23.3, p < 0.001); mean (SD) was 3.8 (0.1) years in BR-N-, 3.7 (0.1) years in BR-N+, 3.4 (0.3) years in BR + N-, and 3.0 (0.3) years in BR + N+. Further, the BR + N- showed more JR than the BR-N- subgroup (p < 0.01), while BR + N+ similarly showed more JR than the BR-N+ subgroup (p < 0.001).In the NAC, the BR- group had a mean age of 51.6 (7.0) years at baseline but 57.7 (8.7) years at final follow up during nitisinone therapy and showed only 7 incident JR. The BR+ group had an age at baseline of 57.4 (8.5) years and had undergone 94 JRs at baseline. Conclusion: The incidence of arthroplasty was earlier and more frequent after the first JR and was not affected by nitisinone.